Performance Improvement for Wireless Sensors Networks by Adopting Hybrid Subcarrier Intensity Modulation Over Exponentiated Weibull Turbulence Channels - Yi Wu (IEEE Access, 2020)
We conduct a research on free space optical (FSO) communication system that is applied for transmission in wireless sensor networks (WSN), which is based on the hybrid pulse position modulation-binary phase shift keying-subcarrier intensity modulation (PPM-BPSK-SIM) undergoes novel Exponentiated Weibull fading channels. When battery-charged sensor transmission nodes with limited energy is transmitted, it is vital to study the performance of the transmission link. We have derived the exact joint probability function of the transmission link when the atmospheric turbulence and pointing errors are considering. On the basis of them, the unconditional average bit error rate (BER) for hybrid PPM-BPSK-SIM is derived, then the closed expression of the outage probability and the average channel capacity are also derived. Research results indicates that increasing the receiver aperture by aperture averaging effect can distinctly improve the performance of the link. Additionally, for any circumstances of atmospheric turbulence and pointing errors, by combining the utilization of hybrid PPM-BPSK-SIM modulation and symbol with average length greater than eight, the average BER performance can be conspicuously enhanced. The outage probability and average channel capacity of the FSO link are jointly affected by atmospheric turbulence and pointing error, and optimization strategies in different scenarios are given by our research.